IMPLEMENTING 360-DEGREE FEEDBACK TO IDENTIFY DEVELOPMENT AREAS FOR SUPERINTENDENT MINING OPERATION DIVISION A CASE STUDY IN PT KALTIM PRIMA COAL - Rimbayati, Wiwin
PT Kaltim Prima Coal (KPC) is a coal mining company operating in East Kalimantan, Indonesia. KPC employs more than 4000 people in its businesses. To ensure the employee's competencies fit the company requirements, an annual assessment is carried out for the first 3 (three) years of occupying a specific position. However, after completing 3 (three) years of development, no re-assessment of competence is carried out. Meanwhile, KPC is recognized that managing employee's performance necessitates ongoing development. Employees in higher-level positions, on the other hand, typically receive less feedback from others. This is because it is assumed that employees in higher positions are, by definition, more capable. Another explanation is that people are hesitant to provide feedback to higher position employees due to the culture. Furthermore, employees, particularly leaders, are extremely busy at work and have little time to conduct self-assessment and analyze their level of competence.